2021
DOI: 10.3389/fneur.2021.757219
|View full text |Cite
|
Sign up to set email alerts
|

Improving Diagnosis and Prognosis in Acute Severe Brain Injury: A Multimodal Imaging Protocol

Abstract: Multi-modal neuroimaging techniques have the potential to dramatically improve the diagnosis of the level consciousness and prognostication of neurological outcome for patients with severe brain injury in the intensive care unit (ICU). This protocol describes a study that will utilize functional Magnetic Resonance Imaging (fMRI), electroencephalography (EEG), and functional Near Infrared Spectroscopy (fNIRS) to measure and map the brain activity of acute critically ill patients. Our goal is to investigate whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Besides EEG (and ERPs) and fMRI, the prognostic value of other emerging techniques such as functional near-infrared spectroscopy or transcranial magnetic stimulation combined with EEG (TMS-EEG) will be investigated in the future in the acute clinical setting. 29,30 Finally, an effort has been undertaken to investigate the added value of multimodal assessment, such as done in the study of Amiri et al 31 However, they failed to prove the added value of the combination of EEG and fMRI data and using machine learning to predict 12month outcome while EEGs alone-as well as thorough repeated neurological assessment alone-were good models to predict outcome at that time point. Mortality rates were not addressed systematically, but we found similar death rates for patients with CMD (33%) compared with non-CMD patients (30.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Besides EEG (and ERPs) and fMRI, the prognostic value of other emerging techniques such as functional near-infrared spectroscopy or transcranial magnetic stimulation combined with EEG (TMS-EEG) will be investigated in the future in the acute clinical setting. 29,30 Finally, an effort has been undertaken to investigate the added value of multimodal assessment, such as done in the study of Amiri et al 31 However, they failed to prove the added value of the combination of EEG and fMRI data and using machine learning to predict 12month outcome while EEGs alone-as well as thorough repeated neurological assessment alone-were good models to predict outcome at that time point. Mortality rates were not addressed systematically, but we found similar death rates for patients with CMD (33%) compared with non-CMD patients (30.5%).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the DMN and FPC play a critical role in normal consciousness ( Demertzi et al, 2014 ; Stender et al, 2014 ). Previous work has shown that disruption in these networks could be a potential marker for patients who are likely to suffer from a disorder of consciousness ( Demertzi et al, 2014 ; Stender et al, 2014 ; Kazazian et al, 2021 ). Therefore, extracting these networks at the single-subject level illustrates the potential of fNIRS as a tool for assessing awareness at the bedside, longitudinally and with low cost.…”
Section: Discussionmentioning
confidence: 99%
“…However, this subjective approach might not be beneficial for all patients. It has been hypothesized that objective prognosis based on physiological measurements could support this decision-making and eventually improve the quality of individual treatment strategies (5,6).…”
Section: Introductionmentioning
confidence: 99%